2013
DOI: 10.1364/boe.4.000364
|View full text |Cite
|
Sign up to set email alerts
|

Imaging axonal transport in the rat visual pathway

Abstract: A technique was developed for assaying axonal transport in retinal ganglion cells using 2 µl injections of 1% cholera toxin b-subunit conjugated to AlexaFluor488 (CTB). In vivo retinal and post-mortem brain imaging by confocal scanning laser ophthalmoscopy and post-mortem microscopy were performed. The transport of CTB was sensitive to colchicine, which disrupts axonal microtubules. The bulk rates of transport were determined to be approximately 80–90 mm/day (anterograde) and 160 mm/day (retrograde). Results d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 93 publications
4
41
0
Order By: Relevance
“…Beyond its use as a neuronal tracer (see transport section above), retrogradely transported CTB effectively labels RGC cell bodies in the retina (Abbott et al, 2013(Abbott et al, , 2014. Recent studies from our group have shown CTB labeling in the cytoplasm and axons of RGCs after SC application, showing good correspondence with the RGC marker Brn3a (Fig.…”
Section: Cholera Toxin B (Ctb)mentioning
confidence: 71%
See 3 more Smart Citations
“…Beyond its use as a neuronal tracer (see transport section above), retrogradely transported CTB effectively labels RGC cell bodies in the retina (Abbott et al, 2013(Abbott et al, , 2014. Recent studies from our group have shown CTB labeling in the cytoplasm and axons of RGCs after SC application, showing good correspondence with the RGC marker Brn3a (Fig.…”
Section: Cholera Toxin B (Ctb)mentioning
confidence: 71%
“…1D, E, H and I). Disruption of AT by intravitreal injection of colchicine, a toxin that interferes with microtubule polymerization, reduces CTB-Alexa488 staining along all of the intra-retinal RGC plasma membrane (Abbott et al, 2013), confirming that CTB intracellular movement is by active transport.…”
Section: Application Of Actively Transported Moleculesmentioning
confidence: 83%
See 2 more Smart Citations
“…CTB can be injected intravitreally in mice and rats and detected in the retina, optic nerve and superior colliculus as the molecule is transported along RGCs. 16,17 Visualizing Components Involved in Axonal Transport…”
Section: Neuronal Tracersmentioning
confidence: 99%